IDENTIFICATION OF WORK-FAMILY BOUNDARY MANAGEMENT STYLES: TWO-STEP CLUSTER ANALYSIS AMONG TEACHERS IN PRIMARY, SECONDARY AND UNIVERSITY EDUCATION (Annual of the Faculty of Philosophy in Skopje, 2023)
The aim of this exploratory study was to identify work-family management boundary profiles on the base of four work-family boundary flexibility dimensions and two types of work-family transitions employed for demarcation/distinction between these two domains. The sample consisted of 143 participants (female=99, mean age=42.50±9.74 years), teachers at university, secondary and primary schools in Macedonian context.Two-step cluster analysis revealed two clusters. Participants in the in the first cluster scored below average on work flexibility ability and on average considering work flexibility willingness, above the average on family flexibility willingness and relatively higher on family flexibility ability and showed very low frequency of transitions from work to family domain, and occasional family-to-work transitions. Participants clustered in the second subgroup showed high ability and willingness to flex work, scored relatively high on family flexibility willingness, expressed strong ability to flex family boundary domain, with occasional moves from work to family domain and more frequent transitions from family to work.Further analyses performed to explore characteristics of both clusters showed that 82.7% of secondary school teachers and 87.5% of primary school teachers were grouped in cluster 1, while most of the university teachers (81.8%) tend to the cluster 2. Equal percentage of male (50%) and female (50%) study participants were distributed across clusters, however cluster 2 consisted predominantly (80.2%) of female participants. Participants in two clusters were found to differ in job satisfaction and family-to-work conflict, whereas differences in regard to life satisfaction, work-to-family conflict, age and number of children were not registered.It could be concluded that cluster/profile 1 was characterized with moderated control over work boundaries, whereas cluster 2 implied to reactive profile with pliable and permeable boundaries of work and family domains.
Keywords: boundary management profiles; work-family flexibility; work-family permeability; two-step cluster analysis